2009
DOI: 10.1017/s1092852900020411
|View full text |Cite
|
Sign up to set email alerts
|

HF-rTMS Treatment in Medication-Resistant Melancholic Depression:Results from18FDG-PET Brain Imaging

Abstract: Introduction: High frequency repetitive tran-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
47
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 75 publications
(51 citation statements)
references
References 67 publications
3
47
0
1
Order By: Relevance
“…Given the role of the pgPFC in emotion-regulative processes (Ochsner and Gross 2005) the observed enhanced functional connectivity between sgACC and pgPFC could be essential for the suppression of depressive symptoms. In addition, it has been reported that AD responders show higher pgACC metabolic states and electrophysiological activity than AD nonresponsive patients (Mayberg et al 1997;Pizzagalli et al 2001 we found that a positive clinical response was associated with increases in both (dorsolateral) prefrontal and pgACC (BA 32) metabolic activities (Baeken et al 2009). …”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…Given the role of the pgPFC in emotion-regulative processes (Ochsner and Gross 2005) the observed enhanced functional connectivity between sgACC and pgPFC could be essential for the suppression of depressive symptoms. In addition, it has been reported that AD responders show higher pgACC metabolic states and electrophysiological activity than AD nonresponsive patients (Mayberg et al 1997;Pizzagalli et al 2001 we found that a positive clinical response was associated with increases in both (dorsolateral) prefrontal and pgACC (BA 32) metabolic activities (Baeken et al 2009). …”
Section: Discussionsupporting
confidence: 59%
“…Nevertheless, the stronger FC observed after successful HF-rTMS treatment between the sgACC and parts of the left superior frontal gyrus (BA 10) suggests a reversal of neuronal activity within these networks. This reversal pattern has also been reported after successful psychopharmacotherapy and neurostimulation techniques such as DBS and rTMS (Mayberg et al 2005;Drevets et al 2008 b;Baeken et al 2009). These brain imaging data could indicate that this reversal pattern is essential for depression improvement, regardless of the used intervention.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…In a recent double-blind sham-controlled crossover trial, MDD patients who were classifi ed as clinical responders aft er highfrequency rTMS exhibited a stronger correlation between the subgenual anterior cingulated cortex and the perigenual prefrontal cortex at the resting-state functional MRI . As known, increased anterior cingulate cortex activity has been identifi ed as a positive predictive factor for response to rTMS in MDD (Baeken et al 2009). Moreover, the ability of rTMS to modulate the subgenual cingulate cortex is of signifi cant interest given its strong and consistent association with MDD (Drevets et al 1997;Mayberg et al 2005).…”
Section: Discussionmentioning
confidence: 98%
“…Without coconcomitant brain imaging techniques is speculative to assume that our clinical HF-rTMS effects on psychomotor improvement are associated with a 'hypodopaminergic state'. In addition, whether these effects on psychomotor retardation are mediated by dysfunctions within fronto-cingulate networks or by the spreading of neuronal activity to the (pre)motor cortical areas remains to be answered (Knoch et al, 2006;Baeken et al, 2009). …”
Section: Discussionmentioning
confidence: 99%